5 - Exploitation Agricole des Berges : Une Strategie D’Adaptation aux Changements Climatiques Destructrice des Forets Galleries dans La Plaine de L’oti - Badabaté Diwédiga Iwédiga,; Komlan Batawila,; Kpérkouma Wala,; Koffi Hounkpè,; Apeti Koffi Gbogbo,; Sêmihinva Akpavi,; Thierry Tatoni,; Koffi Akpagana, (African Sociological Review, 2013)
This paper is a survey of the dynamic of human activities bound to waterways and their impact on the natural ecosystems. it reveals the predominance of food cropping and gardening during the rainy and non-rainy seasons. These agricultural activities are flourishing but are met with such natural constraints as floods. As a strategy for economic survival, activities such as breed- ing and pottery are adopted. The dendrometric data collected in farms, fallows and riparian forests, show negative impact of these anthropogeneous practices.